The white nuns : Cistercian abbeys for women in medieval France - Berman, Constance H. (Middle Ages series., 2018)
The White Nuns considers Cistercian women and the women who were their patrons in a clear-eyed reading of narrative texts and administrative records. In rejecting long-accepted misogynies and misreadings, Constance Hoffman Berman offers a robust model for historians writing against received traditions.